Uptake and Cytotoxicity Characterization of Radioiodine in MCF-7 and SKBR3 Breast Cancer Cell Lines - A. Elliyanti; V.Y. Susilo; S. Setiyowati; M. Ramli; J.S. Masjhur; T.H. Achmad (PPIKSN-BATAN, 2016)
Radioiodine is an effective and low-risk therapy modality in well-differentiated thyroid cancer patients post near-total thyroidectomy. Extra thyroidal tumors such as breast cancer are known to be able to uptake radioiodine. The aim of this study was to analyze the uptake, efflux and cytotoxicity of radioiodine for two molecular types of breast cancer cell lines. Two types of breast cancer cell lines were used in this study, MCF-7 (luminal A type) and SKBR3 (HER2 type). The HaCaT cell line was used as normal cells. Iodine-125 (I-125)was used to measured radioiodine uptake and efflux. Clonogenic assay was used to assess cytotoxicity of iodine-131 (I-131) based on the tested cell reproductive ability. The radioiodine uptake in SKBR3cells was found to be higher than that of MCF-7 and HaCaT cells atp<0.05. The reproductive ability of MCF-7 cells are lower than SKBR3 cells at p<0.05. Both breast cancer cells have lessreproduction ability than HaCaT cells at p<0.05. Both types of breast cancer cells present the ability to uptake radioiodine and show a high sensitivity to radioiodine exposure. Normal cells also demonstrate an ability to uptake radioiodine. However, they have a better tolerance to the amount of I-131 exposure. These findings could potentially lead to the use if I-131 for ablative therapy in breast cancer, similiar to its use in the treatment of thyroid cancer.Received: 4 October 2015; Revised: 14 August 2016; Accepted: 2 September 2016